Clinical Outcomes among Type 2 Diabetes Mellitus Patients: Before and after Universal Health Coverage in Indonesia - Anggriani, Yusi; Purwanggana, Agus; Restinia, Mita (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was carried out to analyze the impact of universal health coverage in Indonesia, known as Jaminan Kesehatan Nasional (JKN) on percentage of patients who did fasting blood glucose (FBG) tests each hospital visit and clinical outcomes (CO) in type 2 diabetes mellitus (T2DM) patients. Methods: We conducted a longitudinal retrospective study to collect the data from 6-month before JKN and 1-year after JKN at 3 hospitals in Jakarta Province. All T2DM outpatients' services using Asuransi Kesehatan (ASKES) with at least 6 hospital visits were included. The subject with double insurances and died before implementation of JKN were excluded. The clinical outcome before and after JKN were compared with Wilcoxon test. Results: Total samples that collected were 296 patients divided to predominance female with 166(56%) and male 125(44%). From the data, it seemed that there were no all patients who did FBG test. We founded 50% of patients had FBG test before JKN. Meanwhile, the percentage at the beginning of JKN tended to be lower about 37% than before JKN. Number of patiens decreased associate with JKN but number of hospital visit increased. Based on FBG level, 17(9.19%) patients had better CO and this number increased slightly after JKN to 22(11.89%). In contrast, patients with worse FBG level decreased about 9%. More patients had bad stable and less patients had good stable FBG level. Statistical analysis showed that CO between before and after JKN had P value 0.404 among T2DM outpatients in Type A Hospitals and P value 0.877 in Type B Hospital. Conclusion: Implementation of JKN had impact to decrease percentage of patients who did FBG tests and number of patients but raised hospital visit. CO was different significantly between before and after JKN among T2DM outpatients in Type A Hospitals but was no different in Type B Hospital.